Ethnicité et sexuation ordinaire dans un foyer pour jeunes femmes en difficulté sociale - El Golli, Wassim (Hommes & migrations, 2011)
Chargés d’une autorité et d’une mission publiques, les travailleurs sociaux peuvent être conduits à relayer dans leur pratique certaines représentations négatives attachées aux populations dont ils ont la charge. Dans une maison éducative à caractère social, l'accompagnement de jeunes femmes d’origine étrangère n’échappe pas à une approche soumise au prisme du sexe et de l’origine ethnique. La question du traitement de leur sexualité au sein du foyer permet de saisir le jeu des stéréotypes qui déterminent en sourdine les rapports sociaux.
https://journals.openedition.org/hommesmigrations/734
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; france; justice sociale; paris; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques

Honor killings in the Middle East and North Africa: a systematic review of the literature - Kulczycki, Andrzej; Windle, Sarah (Violence against women, 2011)
A systematic review of the research literature on honor killings in the Middle East and North Africa (MENA) indicates a paucity of studies relative to the presumed magnitude of the problem. Forty articles were reviewed and critically appraised, of which only 9 contained primary data and 11 presented original secondary analyses. Despite a recent increase in published studies, persistent methodological limitations restrict the generalizability of findings. Most studies focus on legal aspects, determinants, and characteristics of victims and perpetrators. Victims are mostly young females murdered by their male kin. Unambiguous evidence of a decline in tolerance of honor killings remains elusive.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; cours; droits des femmes*; féminisme islamique; maghreb; moyen-orient; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sex2283; sexisme; systèmes d'oppressions; thématiques; violences

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis